2015
DOI: 10.1002/2014ja020657
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric response to CIR‐induced recurrent geomagnetic activity during the declining phase of solar cycle 23

Abstract: This paper presents an epoch analysis of global ionosphere responses to recurrent geomagnetic activity during 79 corotating interaction region (CIR) events from 2004 to 2009. The data used were GPS total electron content (TEC) data from the Madrigal Database at the Massachusetts Institute of Technology Haystack Observatory and the electron density (Ne) data obtained from CHAllenging Minisatellite Payload (CHAMP) observations. The results show that global ionosphere responses to CIR events have some common feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…At midlatitudes where electric fields are small, the change in thermospheric composition is probably the most suitable mechanism to explain the f o F 2 decrease observed by Denton et al [2009]. This is well consistent with the observations, where global decreases in the O/N 2 ratio during magnetic storms were reported [Crowley et al, 2008;Zhang et al, 2014;Chen et al, 2015].…”
Section: Decrease Of F O Fsupporting
confidence: 90%
“…At midlatitudes where electric fields are small, the change in thermospheric composition is probably the most suitable mechanism to explain the f o F 2 decrease observed by Denton et al [2009]. This is well consistent with the observations, where global decreases in the O/N 2 ratio during magnetic storms were reported [Crowley et al, 2008;Zhang et al, 2014;Chen et al, 2015].…”
Section: Decrease Of F O Fsupporting
confidence: 90%
“…Early studies of storm time TEC response were obtained by measuring the Faraday rotation of transionospheric radio signals reflected from the moon [ Evans , ; Taylor , ] and later broadcast by geostationary and low Earth orbit spacecraft [e.g., Hibberd and Ross , ; Klobuchar et al , ; Mendillo , ; Hearn , ; Lanzerotti et al , ; Balan and Rao , ]. More recent statistical studies have used the differential time and phase delay of Global Positioning System (GPS) signals to measure the storm time TEC response over both regional [ Stankov et al , ; Borries et al , ; Chen et al , ] and global scales [ Zhao et al , ; Liu et al , ; Immel and Mannucci , ]. Most TEC studies have found that positive storm effects tend to occur within the first 24 h after onset while the subsequent negative phase may persist for up to several days [e.g., Mendillo , ].…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal variations in thermospheric circulation often produce stronger and longer‐lasting positive/negative TEC changes during winter/summer [ Liu et al , ], although some studies have reported the largest negative storm effects during equinox rather than in summer [ Mendillo and Klobuchar , ; Stankov et al , ]. The American longitude sector has been shown to exhibit the largest positive storm response in comparison with other geographic regions [ Zhao et al , ; Chen et al , ] due to the local magnetic dipole tilt and proximity to the South Atlantic Anomaly [ Yizengaw et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The periodic occurrence of CIRs/HSSs and its effect suggest a possibility for forecasting the ionospheric disturbance during recurrent geomagnetic activities. To fully understand the ionospheric behavior during CIR events, further studies are necessary on the characteristic and commonality of the ionospheric response to CIR/HSS‐induced geomagnetic activity [ Wang et al ., ; Burns et al ., ; Solomon et al ., ; Liu et al ., ; Verkhoglyadova et al ., ; Chen et al ., ]. Burns et al .…”
Section: Introductionmentioning
confidence: 99%